2009
DOI: 10.1007/s11661-008-9754-4
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of the Nonisothermal Decomposition of Palladium Acetylacetonate Investigated by Thermogravimetric and X-Ray Diffraction Analysis Determination of Distributed Reactivity Model

Abstract: The nonisothermal decomposition process of the powder sample of palladium acetylacetonate [Pd(acac) 2 ] was investigated by thermogravimetric (TG) and X-ray diffraction (XRD) techniques. The experimental TG and differential thermogravimetric (DTG) curves were obtained at different heating rates (b = 2°C min À1 , 5°C min À1 , 10°C min À1 , 20°C min À1 , and 30°C min À1 ) under a pure nitrogen (N 2 ) atmosphere. The kinetic triplet (A, E a , and model function f(a)) was determined using different kinetic methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The particle size is determined by several factors as decomposition of the noble metal source compounds, seed formation rates, and diffusion properties. While both platinum acetylacetonate and palladium acetylacetonate decompose around 200 °C, 31,32 the activation energy of the diffusion of platinum is 1.4À1.5 times higher than that in the case of palladium 33 which leads to a slower surface diffusion of platinum and results in nanoparticle formation from a smaller area around the seed.…”
Section: Resultsmentioning
confidence: 95%
“…The particle size is determined by several factors as decomposition of the noble metal source compounds, seed formation rates, and diffusion properties. While both platinum acetylacetonate and palladium acetylacetonate decompose around 200 °C, 31,32 the activation energy of the diffusion of platinum is 1.4À1.5 times higher than that in the case of palladium 33 which leads to a slower surface diffusion of platinum and results in nanoparticle formation from a smaller area around the seed.…”
Section: Resultsmentioning
confidence: 95%
“…One interesting observation is that the primary particle size seems to stop growing or grow very slow in the case of Pd(acetate) 2 , whereas for Pd(acac) 2 , the particles detected by SAXS continue to grow. It is reported that the thermal decomposition of Pd(acac) 2 is a single-step process that forms Pd and acac . For Pd(acetate) 2 , in the inert atmosphere, the major decomposition product is Pd, whereas in air, the thermal decomposition of Pd(acetate) 2 is more complicated, and other Pd-containing species are also formed .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the thermal decomposition of Pd(acac) 2 is a single-step process that forms Pd and acac. 43 For Pd(acetate) 2 , in the inert atmosphere, the major decomposition product is Pd, whereas in air, the thermal decomposition of Pd(acetate) 2 is more complicated, and other Pd-containing species are also formed. 32 In our experiment, the Pd(acac) 2 and Pd(acetate) 2 are heated in solution.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the reaction model can be numerically reconstructed by the values of the pre-exponential factor A and the activation energy E. The dependence of time and temperature on the reaction rate can be also obtained. At present, thermal analysis kinetics has been applied in the fields of ceramics, complexes, polymers, biopolymers, and energetic materials [30][31][32][33][34][35], determining reaction mechanism during materials decomposition and synthesis. In this work, the nonisothermal method was used to investigate the thermal decomposition and phase formation mechanism of Bi2212 precursors with different heating rates.…”
Section: Introductionmentioning
confidence: 99%